Hybrid Repair of a Thoracoabdominal Aortic Aneurysm as a Bailout Option from Open Repair - Camila Esquetini-Vernon; Houssam Farres; Mohamed Rajab; Christopher Jacobs; Young Erben (Annals of Vascular Surgery - Brief Reports and Innovations)
Introduction: Thoracoabdominal aortic aneurysm (TAAA) repair remains associated with considerable morbidity and mortality. An endovascular repair offers a less invasive alternative but is limited by the availability of devices and anatomical constraints. A hybrid approach, combining open visceral debranching with endovascular exclusion, is a viable option for high-risk patients unsuitable for complete open repair. Clinical summary: We report a three-stage hybrid repair of a type IV TAAA in a 62-year-old male with a history of hypertension, hyperlipidemia, seizures, and severe aortic stenosis post-transcatheter aorta valve replacement (TAVR). This repair was initially planned for a single-stage operation. However, due to significant inflammatory findings at the time of the surgical intervention, a staged repair was performed. The inflammation caused significant difficulty in the aorta and vessel dissection and acute blood loss, making this staged approach the safest and most feasible option. On the initial operation, the patient underwent visceral debranching, followed by endovascular thoracic aortic stent placement and a final, physician-modified endograft addressing the right renal artery and exclusion of the aortic aneurysm. Conclusion: This case illustrates the successful use of a staged hybrid approach for TAAA repair when the initial operation cannot be completed as planned due to inflammatory features found at the time of aortic exposure. It demonstrates a pivot to the initial surgical plan yielding a favorable outcome with the preservation of renal function in a high-risk and complex patient.